Comparison of Two X-ray Detection Systems Used to Investigate Properties of Normal and Malignant Breast Tissues - Alaroui, Duaa (My University, 2018)
The present study was implemented using two different X-ray detection systems; a monochromatic X-ray system for X-ray Fluorescence (XRF) and Angular Dispersive X-ray Diffraction (ADXRD) techniques, and a combined Polarized Energy Dispersive X-ray Fluorescence (PEDXRF) and Energy Dispersive X-ray Diffraction (EDXRD) system. As both of these systems involve different techniques, the primary objective of this study was to evaluate the performance and accuracy of each system using results achieved from XRF measurements. The assessment of the two systems was carried out by investigating invasive ductal carcinoma (IDC) of breast and normal surrounding breast tissues. The results established from the two XRF systems are in a very good agreement with each other. The statistical analysis reveals a significant and measurable increase at P<0.01 in the concentration of K, Ca, Zn, Rb and Fe (P<0.05) in the tumor tissue when compared with the healthy tissue. However, the levels of Cl, Cu and Br attained by both systems have not demonstrated a statistically significant difference between the normal and cancerous tissues. Investigating the structural components of the same breast tissues using of the X-ray Diffraction (XRD) spectrometers incorporated in both systems indicated a statistically significant difference in the components of normal and malignant samples. Furthermore, the results have shown a remarkable increase in the fibrous and water contents of the tumour tissue at P<0.01, and a significant increase in the adipose content of the normal tissue at P<0.01. The results acquired from both XRD approaches were shown to be statistically compatible with each other. Overall, the comparisons between the two X-ray detection systems have shown tremendous results for the combined PEDXRF and EDXRD system for the purpose of classifying normal and tumor breast tissues.
Keywords: x-ray, x-ray fluorescence, Breast cancer, x-ray diffraction